Efforts to Increase Knowledge about Healthy Houses and Healthy Toilets in the Community in Ds. Lampah, Kedamean District, Gresik Regency - Hasanah, alsabila Maulidah; Roebbi, aadiyah; Wulandari, Catur; Herlambang, Teguh (Journal of Health Community Service, 2023)
A house is a building that functions as a suitable place to live, as a means for family development, a reflection of the dignity and dignity of its residents, and an asset for its owner (Ministry of PUPR 2016). The problem in Lampah Village is that there are still many houses that do not meet the criteria for a healthy house. The purpose of this community service is to provide health education related to the criteria for healthy houses and healthy latrines so that it is hoped that the community knows and is able to implement healthy houses and latrines in their homes. The method used in this community service is interviews with the community using questionnaire media related to healthy houses and healthy latrines. Then after an interview, then lectures, discussions and leaflets were given. The target of this community service is the residents of Pondok Hamlet. During the event, residents enthusiastically listened and actively asked questions, overall the activity went smoothly, the community gave a good response to the event that had been held.